The risk of thromboembolic events with early intravenous 2‐ and 4‐g bolus dosing of tranexamic acid compared to placebo in patients with severe traumatic bleeding: A secondary analysis of a randomized, double‐blind, placebo‐controlled, single‐center trial. (29th June 2022) - Spinella, Philip C.; Bochicchio, Kelly; Thomas, Kimberly A.; Staudt, Amanda; Shea, Susan M.; Pusateri, Anthony E.; Schuerer, Douglas; Levy, Jerrold H.; Cap, Andrew P.; Bochicchio, Grant
Abstract: Background: Screening for the risk of thromboembolism (TE) due to tranexamic acid (TXA) in patients with severe traumatic injury has not been performed in randomized clinical trials. Our objective was to determine if TXA dose was independently‐associated with thromboembolism. Study Design and Methods: This is a secondary analysis of a single‐center, double‐blinded, randomized controlled trial comparing placebo to a 2‐g or 4‐g intravenous TXA bolus dose in trauma patients with severe injury. We used multivariable discrete‐time Cox regression models to identify associations with risk for thromboembolic events within 30 days post‐enrollment. Event curves were created using discrete‐time Cox regression. Results: There were 50 patients in the placebo group, 49 in the 2‐g, and 50 in the 4‐g TXA group. In adjusted analyses for thromboembolism, a 2‐g dose of TXA had an hazard ratio (HR, 95% confidence interval [CI]) of 3.20 (1.12–9.11) ( p  = .029), and a 4‐g dose of TXA had an HR (95% CI) of 5.33 (1.94–14.63) ( p  = .001). Event curves demonstrated a higher probability of thromboembolism for both doses of TXA compared to placebo. Other parameters independently associated with thromboembolism include time from injury to TXA administration, body mass index, and total blood products transfused. Discussion: In patients with severe traumatic injury, there was a dose‐dependent increase in the risk of at least one thromboembolic event with TXA. TXA should not be withheld, but thromboembolism screening should be considered for patients receiving a dose of at least 2‐g TXA intravenously for traumatic hemorrhage.